1998
DOI: 10.1016/s0022-2275(20)32562-1
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of apoB- and apoA-I-containing lipoproteins by chick kidney

Abstract: Previous studies showed that chick kidney is a site of synthesis of apolipoprotein (apo) B(B-100) and A-I. Aims of the present study were: a ) to compare apoB and apoA-I production in chick kidney and liver; b ) to investigate whether kidney apolipoproteins were secreted as constituents of lipoproteins; and c ) to define the cellular sites of renal apolipoprotein synthesis. Kidney and liver slices taken from the same animals were incubated with 35 S-labeled amino acids and radioactive apoB and apoA-I were immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 42 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…In the current study, we demonstrated that the apoB mRNA is highly expressed in the liver of laying Taiwan Country chickens similar to what was reported by Dixon et al (1992) in Leghorn chickens. The results suggest that in the chicken, liver is the major site for production of apoB, although some apoB synthesis can be found in the kidney (Tarugi et al, 1998).…”
Section: Discussionmentioning
confidence: 91%
“…In the current study, we demonstrated that the apoB mRNA is highly expressed in the liver of laying Taiwan Country chickens similar to what was reported by Dixon et al (1992) in Leghorn chickens. The results suggest that in the chicken, liver is the major site for production of apoB, although some apoB synthesis can be found in the kidney (Tarugi et al, 1998).…”
Section: Discussionmentioning
confidence: 91%
“…Initially, it was believed that E 2 did not play any role in the synthesis of ApoB in the kidney or intestine (Kirchgessner et al, 1987;Lazier et al, 1994), while it was shown to directly control the production of ApoVLDL-II in the embryonic kidney (Lazier et al, 1994). However, the hen's kidney produces generic VLDL and HDL (Bensadoun and Rothfeld, 1972;Tarugi et al, 1998), with the generic VLDL secreted by cells of the proximal tubules. Thus, generic VLDL from the kidney during the laying cycle was proposed to provide the necessary energy to tissues evaded by VLDLy (Walzem et al, 1999).…”
Section: Activation Of the Kidneymentioning
confidence: 99%
“…Most apoA-I is synthesized in the liver and intestine, although small amounts of apoA-I are produced in avian nerve tissue (10) and kidney (11). ApoA-I is translated as a preproprotein (12) and, after cleavage of the 18-amino acid signal peptide, the proprotein is secreted into the plasma, where the 6-amino acid propeptide is removed by cleavage through an unidentified metalloprotease (13).…”
mentioning
confidence: 99%